Space and the parietal cortex. - Husain, M; Nachev, P (2007)
Current views of the parietal cortex have difficulty accommodating the human inferior parietal lobe (IPL) within a simple dorsal versus ventral stream dichotomy. In humans, lesions of the right IPL often lead to syndromes such as hemispatial neglect that are seemingly in accord with the proposal that this region has a crucial role in spatial processing. However, recent imaging and lesion studies have revealed that inferior parietal regions have non-spatial functions, such as in sustaining attention, detecting salient events embedded in a sequence of events and controlling attention over time. Here, we review these findings and show that spatial processes and the visual guidance of action are only part of the repertoire of parietal functions. Although sub-regions in the human superior parietal lobe and intraparietal sulcus contribute to vision-for-action and spatial functions, more inferior parietal regions have distinctly non-spatial attributes that are neither conventionally 'dorsal' nor conventionally 'ventral' in nature.